2015
DOI: 10.1590/s1806-92902015000600002
|View full text |Cite
|
Sign up to set email alerts
|

Milk composition and its relationship with weaning weight in Charolais catte

Abstract: -To determine the effects of a number of non-genetic factors on milk components and estimate their indirect relationships with weaning weight (WW205), the percentages of protein, fat, lactose and solids non-fat in Charolais cows from Mexico were estimated. Lactation period (LP) and calving season (CS) had significant effects on protein and fat, whereas lactose and solids non-fat were only affected by the LP. Sire line and age of the dam had significant effects on calf birth weight, while CS affected WW205. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…This result was higher than the weaning weight of several Indonesian native cattle are Bali 90.5±15.46,Sumba Ongole 113.67±25.24 kg, Brahman cross 107.13+19.25 kg and 44.68+11.00 kg for Aceh (Praharani, 2009;Kaswati et al, 2013;Putra et al, 2014). It was also lower than weaning weight of Charolais 229.10±12.73 kg, Hungarian Grey 191±5.05 kg, Hungarian Simmental 236±3.40 kg, Angus 212±3,61 kg, Hereford 204±5.06 kg, Blonde d'Aquitaine 242±7.95 kg, Limousin 203±2.99 kg, Angus-Nellore 247.74±5.63 and Simmental-Nellore 248.16±7.31 (Contreras et al, 2015;Szabó et al, 2012;Szabó et al, 2013 andÍtavo et al, 2014). The difference in the weaning weight was caused by the difference of the weaning ages and breeds.…”
Section: Weaning Weightmentioning
confidence: 84%
“…This result was higher than the weaning weight of several Indonesian native cattle are Bali 90.5±15.46,Sumba Ongole 113.67±25.24 kg, Brahman cross 107.13+19.25 kg and 44.68+11.00 kg for Aceh (Praharani, 2009;Kaswati et al, 2013;Putra et al, 2014). It was also lower than weaning weight of Charolais 229.10±12.73 kg, Hungarian Grey 191±5.05 kg, Hungarian Simmental 236±3.40 kg, Angus 212±3,61 kg, Hereford 204±5.06 kg, Blonde d'Aquitaine 242±7.95 kg, Limousin 203±2.99 kg, Angus-Nellore 247.74±5.63 and Simmental-Nellore 248.16±7.31 (Contreras et al, 2015;Szabó et al, 2012;Szabó et al, 2013 andÍtavo et al, 2014). The difference in the weaning weight was caused by the difference of the weaning ages and breeds.…”
Section: Weaning Weightmentioning
confidence: 84%
“…In addition, several milk traits were extensively affected by breed throughout the lactation time. Milk composition traits such as fat and protein percentages have been used as indicators of milk quality and, together with the amount of milk produced, they can also affect calf performance and system efficiency (Cerdótes et al 2004;Rodrigues et al 2014;Contreras et al 2015). In the present study, the Nellore cows had a greater content of milk fat and protein at 90, 120, 150 and Angus (recipient primiparous ½ Angus-Nellore); Nellore (recipient primiparous Nellore).…”
Section: Discussionmentioning
confidence: 48%
“…Furthermore, milk fat, protein and lactose contents were more positively correlated with marbling, because a higher nutritional value of the milk leads to a greater nutritional contribution to the calves at the very early stages of life, so that greater numbers of multipotent cells can differentiate to become adipocyte cells, improving marbling (Du et al 2010). Contreras et al (2015), studying milk yield and composition of Charolais cows, found a significant correlation between milk lactose and calves weaning weight, but no correlation was found between fat and protein in milk and calves' weight.…”
Section: Discussionmentioning
confidence: 99%
“…Different variants of casein have been related to milk yield and composition and protein content (Caroli et al, 2009). Allegedly, the segregation of variation in these genes might be related through the regulation of milk composition to promote growth through enhanced nutrition from milk composition during the pre-weaning stage in calves (Brown and Brown, 2002;Pacheco et al, 2015). Similarly, leptin gene variation has been reported to be associated with milk yield, live weight, energy balance, feed consumption, and carcass fat content (Buchanan et al, 2002;Liefers et al, 2002;Madeja et al, 2004).…”
Section: Introductionmentioning
confidence: 99%